Congenital peritoneal encapsulation—a rare entity presented with small bowel obstruction. Issue 1 (30th January 2021) - Tojal, André; Marques, Júlio; Coelho, Sandra; Ferreira, Maria-João; Carrilho, Noel; Horta-Oliveira, António; Casimiro, Carlos
Abstract: Congenital peritoneal encapsulation is a rare congenital malformation in which all or part of the small bowel is covered by a thin accessory peritoneal membrane. Despite being usually asymptomatic and an incidental finding during surgery or autopsy, there is a small number of reports in the literature whose diagnosis was established in the context of intestinal obstruction. The authors review the topic and describe a case report undergoing surgery for intestinal obstruction. Intraoperatively, there was a partial peritoneal encapsulation of the small bowel with signs of intestinal malrotation. Peritoneal membrane excision, terminal ileum release and complementary appendicectomy were performed. There was a favorable clinical evolution in the postoperative period. Although rare, it is important to remember this entity in the differential diagnosis of patients with intestinal obstruction, in the absence of other etiologic factors.